Socìal‘no-ekonomìčnì ta polìtiko-pravovì peredumovi stanovlennâ ta rozvitku modernogo samovrâduvannâ u L'vovì u drugìj polovinì XIX stolìttâ - Kiseličnik, Vasil' (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The history of municipal law and local self-government of Lviv’s community occupies a special place in the history of self-government in Ukraine. The idea that Lviv became a “small world” in which the big one (Ukrainian self-government) conducted its European rehearsals represents the originality of their interaction. Summarizing the influence of Lviv on the history of self-government in Ukraine, it is difficult to determine its decisive role in view of the diversity and multiformity of all factors. The dilemma of the city’s openness and its long stay under the influence of different state-building ideas and ideologies immediately arises. On the other hand, its own ability to be a center of public activity and local self-government, to adapt European models of territorial governance is obvious. After all, it was Lviv, being organically and spiritually connected with Europe, that became a transit city in this sphere, from where European self-governing models spread to Ukrainian territory. The “historical breaking point” in the development of Lviv’s community and the forma-tion of modern self-government in Lviv took place in the second half of the 19th century, when the city was a part of the Austrian monarchy. The Habsburg dynasty, extending its sovereignty to more and more regions, did not change, at least initially, the traditional forms of government in those kingdoms, duchies and cities it seized. However, later, in order to preserve the empire, it became necessary to carry out political, legal and economic reforms, which would mean a movement from an absolute monarchy to a constitutional one, from a police state to a state governed by the rule of law.The conditions of socioeconomic development of Lviv after its accession to Austria were radically different from previous times. The city changed its long-standing trading and mil-itary status to administrative and bureaucratic, as Lviv became the capital of a large Austrian province, which immediately introduced the system of central bureaucratic management that existed in the Habsburg monarchy. In general, the history of the economic development of Lviv (local territorial commun-ity) during the Austrian period can be divided into two distinct stages. The initial point that divided these periods was the introduction of modern self-government in 1870 in Lviv according to the norms of the statute, which became an important factor in transforming the life of the local community in all its manifestations. In the 1860s, the socioeconomic foundations for the formation of a new type of municipal self-government were laid, the power of Lviv community increased, and the urban econ-omy was developed. However, further economic growth, in which the Austrian monarchy was interested, was possible only under the conditions of decentralization of state power, namely: recognition and guarantee of local self-government at the legislative level (political and legal preconditions). Such a legal and regulatory basis for the formation and functioning of local self-govern-ment was laid with the adoption of the nationwide Austrian law “On the basic principles of communities’ organization” on March 5, 1862. However, only on August 26, 1870, after changes and additions were made by the com-missions of the city council, the draft statute of Lviv was approved by the Galician Regional Sejm in its final version, and on October 14, 1870, the statute was approved by the Monarch. The granting of the statute to the territorial community in 1870 became the most im-portant historical event on the way to building local democracy in Lviv in this section of the historical period. The formed Lviv community was legalized and became an independent subject of public and state life. With the granting of the statute to the territorial community of Lviv, a new era in the history of self-government of the Lviv community began.
Keywords: preconditions of self-government development; modern self-government; territorial community; Lviv municipal statute